A Pattern of Care Report on the Management of Patients with Squamous Cell Carcinoma of the Anus—A Study by the Italian Association of Radiotherapy and Clinical Oncology (AIRO) Gastrointestinal Tumors Study Group - Franco, Pierfrancesco; Chiloiro, Giuditta; Montesi, Giampaolo; Montrone, Sabrina; Arcelli, Alessandra; Comito, Tiziana; Arcadipane, Francesca; Caravatta, Luciana; Macchia, Gabriella; Lupattelli, Marco; Niespolo, Marina Rita; Munoz, Fernando; et al. (Medicina (Kaunas, Lithuania), 2021)
Background and objectives: The diagnosis and therapy of squamous cell carcinoma of the anus may vary significantly in daily clinical practice, even if international guidelines are available. Materials and Methods: We conducted a pattern of care survey to assess the management of patients with anal cancer in Italy (38 questions). We analyzed 58 questionnaires. Results: Most of the respondents work in public and/or university hospitals (75.8%) in northern Italy (65.5%). The majority (88.0%) treat less than 20 patients/year. Common examinations for diagnosis and staging are anorectal endoscopy (84.5%), computed tomography scan (86.2%) and pelvic magnetic resonance imaging (MRI) (96.5%). The most frequently prescribed dose to primary tumor is 50–54 Gy (46.5–58.6%) for early stage disease and 54–59.4 Gy (62.1–32.8%) for locally advanced cases. Elective volumes are prescribed around 45 Gy (94.8%). Most participants use volumetric intensity modulated radiotherapy (89.7%) and a simultaneous integrated boost (84.5%). Concurrent radiotherapy, 5-fluorouracil and mitomycin is considered the standard of care (70.6%). Capecitabine is less frequently used (34.4%). Induction chemotherapy is an option for extensive localized disease (65.5%). Consolidation chemotherapy is rarely used (18.9%). A response evaluation is conducted at 26–30 weeks (63.9%) with a pelvic MRI (91.4%). Follow-up is generally run by the multidisciplinary tumor board (62.1%). Conclusions: Differences were observed for radiotherapy dose prescription, calling for a consensus to harmonize treatment strategies.